The Role of Cynicism in the Context of Healthcare Apps: Evidence from Indonesia - Setyawan, Didik; Bramantyo, Frederikus; Mahaestri Noor, Finisha; Maminirina Fenitra , Rakotoarisoa (Jordan Journal of Business Administration, 2025)
This study aims to identify the factors influencing cynicism and the impact of cynicism on the usage of healthcare apps and platforms in Indonesia. This work proposes a model to explain the formation of cynicism and its impact on attitude in Indonesia. Data was collected from 200 healthcare app users through an online survey questionnaire. The results of structural equation modeling show that anxiety, negative emotions, and security plays a significant role in forming cynicism. The study also found that cynicism is vital in increasing attitudes toward failure and decreasing attitudes toward learning. These results indicate high cynicism towards healthcare apps due to anxiety, negative emotions, and security, which impact increasing attitudes toward failure and decreasing attitudes toward learning. These findings provide theoretical insight and practical contribution. In addition, limitations and directions for future research are discussed.